Panorama del sector ferroviario en Colombia frente a los desfios del Comercio Exterior entre 2010 a 2020 - Laverde Aricapa, Luisa Fernanda; Platicon Busto, María de los Angeles (Universidad Antonio Nariño, 2022)
The objective of this study is to analyze the panorama of the railway sector in Colombia in the face of the challenges of foreign trade between 2010 and 2020. For this purpose, the structure and behavior of the sector are described, competitive advantages and challenges are sought, finally, identifies the strategies required to strengthen the sector based on foreign trade. At a methodological level, a descriptive study is used, with a qualitative approach, where a literature review is used.